Motivasi dan Minat Belajar Siswa Materi SKI di MTS Muslimat NU Palangka Raya - Saiful Anwar; Santiani Santiani (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to analyze the extent to which motivation influences students' learning interest in the Islamic Cultural History (SKI) subject at MTs Muslimat NU Palangka Raya. The research was prompted by the phenomenon of low student interest in learning, despite the relatively high levels of motivation provided by teachers. A quantitative approach with a descriptive method was employed in this study. The sample consisted of 70 students from grades VII and VIII, selected using a total sampling technique. Data were collected through questionnaires and documentation, and analyzed using simple linear regression with the assistance of SPSS version 25. The results revealed a significant relationship between motivation and learning interest, although the correlation was negative. This is evidenced by a significance value of 0.009, which is less than 0.05, and a correlation coefficient of -0.330. In other words, an increase in motivation appears to be inversely related to students’ interest in the SKI subject. These findings suggest that not all forms of motivation have a positive effect on learning interest, highlighting the need to reevaluate the motivational strategies applied in schools. It is hoped that this study can serve as a reference for educators in developing more effective teaching strategies that can foster student interest in learning in a positive and sustainable